A HOLISTIC APPROACH TO CORPORATE SOCIAL RESPONSIBILITY AS A PREREQUISITE FOR SUSTAINABLE DEVELOPMENT: EMPIRICAL EVIDENCE - Zlatanović, Dejana (Economic Annals, 2015)
The growing importance of sustainable development and corporate social responsibility (CSR) for contemporary organizations demands appropriate holistic tools. The paper highlights how Soft Systems Methodology (SSM), a relevant holistic, i.e., soft systems approach, supports the conceptualization and management of the complex issues of CSR and sustainable development. The SSM’s key methodological tools are used: rich picture, root definitions, and conceptual models. Empirical research compares a selected sample of enterprises in the automotive industry in the Republic of Serbia, to identify possible systemically desirable and culturally feasible changes to improve their CSR behaviour through promoting their sustainable development. Some limitations of this research and of SSM application are discussed. Combining SSM with some other systems approaches, such as System Dynamics or Critical Systems Heuristics, is recommended for future research.